Equivalência de itens e semântica da versão brasileira do EORTC QLQ-FA13 (Revista Brasileira de Pesquisa em Saúde/Brazilian Journal of Health Research, 2018)
Conceptual equivalence of items and semantic equivalence in the Brazilian version of the EORTC QLQ-FA13